Competition and coordination in the Mexican retail market for gasoline - Benjamin Contreras-Astiazaran; René Leal Vizcaíno; Jordán Mosqueda; Alejandrina Salcedo (Banco de México, 2020)
We document the following stylized facts for the Mexican retail market for gasoline using data for 2018-2019: (1) consumer prices adjust slower than wholesale prices; (2) more competition, in the form of a higher density of stations, implies lower markups and lower prices; and (3) more competition implies faster pass-through. However, we find geographical differences in the speed of pass-through that cannot be explained by differences in station density. We conjecture that coordination on high prices could be offsetting competitive pressure in some locations. We build a classifier that separates municipalities into two categories depending on whether the relative price concentration is on "high" prices or "low" prices. In the first type of municipalities, the price concentration is correlated positively with the price level and negatively with pass-through. For concentration in "low" prices the signs of the correlations are reversed.
Keywords: L4; L5; L13; D4; H25; 330; Gasoline; Pass-through; Geographic Competition; Price Coordination